Analisis Penyakit ISPA di Wilayah Kerja UPTD Puskesmas Penyandingan Kecamatan Sosoh Buay Rayap Kabupaten Ogan Komering Ulu - Surwani; Chairil Zaman; Yunilasari (Jurnal Kesehatan Saelmakers PERDANA, 2022)
The development of the health sector is directed at improving the health status of the community, both infectious and non-communicable diseases. One of the infectious diseases is pneumonia or acute respiratory infection. The purpose of this study was to look at the factors associated with the incidence of acute respiratory infection. This study uses a quantitative method with a cross sectional approach. Statistical test using chi square test. Multivariate analysis in this study used multiple logistic regression analysis. In this study, it can be concluded that there is a relationship between work (p = 0.015; OR = 4,838), using masks (p = 0.021; OR = 4.346), use of mosquito venom (p = 0.008; OR = 5,500) and clean and healthy behavior (p = 0.039; OR=3.844) with acute respiratory infection in the Work Area of ??the Puskesmas Pengandingan, Sosoh Buay Termite Sub-district, OKU Regency in 2021. There is no relationship between age (p= 0.333), and smoking habits (p= 4.346) with ARI in the work area of ??the Puskesmas Pengandingan, Sosoh Buay District. Termites in OKU Regency in 2021. The most dominant variable is the use of mosquito venom (p = 0.004; OR = 7,264). Suggestions for Puskesmas Pairing based on the findings of this study can be used by health centers and OKU district health offices in dealing with ARI by reducing or prohibiting the use of mosquito poison.